Preparation for old age in the family. Generational differences in openness to the needs of senior - Błachnio, Aleksandra; Maliszewski, Wojciech J. (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2015)
The phenomenon of an ageing society manifests itself globally. The problems of senior citizens are widespread and address all actors of social life. The growing interestin elderly needs results in a generally positive shift in the understanding of ageing. Today it is well proved that healthy and active ageing requires the support of all family members. Seniors themselves, but also adult children and grandchildren need to revisetheir approach to ageing in order to learn how to take full advantages of the prolongedlife-span and how to adapt to the costs of the natural decline in senescence.
Keywords: ageing; family; needs; life satisfaction